Risk factors of neonatal hypoglycemia in Banda Aceh: A Retrospective Cross-Sectional Study - Aidil Fittriani Ayu; Darnifayanti Darnifayanti; Mulya Safri; Sulaiman Yusuf; Syafruddin Haris; T. M. Thaib (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Hypoglycemia is the most common metabolic disorder in newborns during the first two days of life, with a global prevalence of 5-15% in at-risk populations. This condition can cause permanent neurological damage and intellectual disabilities. Objective: To analyze the risk factors of neonatal hypoglycemia at Dr. Zainoel Abidin Hospital, Banda Aceh. Methods: This retrospective cross-sectional study used medical records from January to December 2024. The key predictors included gestational age, birth weight, maternal diabetes mellitus, eclampsia, and delivery mode. All eligible records (n=448) were included. Data were analyzed using SPSS version 29 with the chi-square test and multiple logistic regression. Hypoglycemia (blood glucose <45 mg/dL within 24 h of birth) was found in 67 (15.0%) infants. Multivariate analysis identified cesarean section as the strongest independent predictor (AOR=3.850; p<0.001), followed by birth weight <2500 g (AOR=6.345; p=0.004), and prematurity <37 weeks (AOR=3.383; p=0.001). In conclusion, cesarean delivery, prematurity, and low birth weight were independent risk factors for neonatal hypoglycemia after multivariate adjustment.